Antiapoptotic Effects of Propolis Extract and Propol on Human Macrophages Exposed to Minimally Modified Low Density Lipoprotein - Claus, Ralf; Kinscherf, Ralf; Gehrke, Christof; Bonaterra, Gabriel; Basnet, Purusotam; Metz, Jürgen; Deigner, Hans-Peter (Arzneimittelforschung, 2000)
An aqueous extract of propolis and the phenolic component of propolis, propol, were assayed for antioxidative and antiapoptotic properties. Both additions inhibited Cu2+-initiated low density lipoprotein (LDL) oxidation as characterized by a reduction of the lag time, reduced the increase of relative electrophoretic mobility during oxidation and markedly diminished apoptosis of human macrophages exposed to minimally modified (mmLDL). Moreover, aqueous propolis extract and propol blocked the mmLDL-induced decrease of glutathione (GSH) and the activation of the transcription factor NF-kB in these cells. The potent phenolic antioxidant propol thus expands the capability of cells to neutralize oxidative stress and to prevent apoptosis and is therefore suggested to significantly contribute to the antiinflammatory and antioxidative effects of propolis.
Keywords: Antioxidants; Low density lipoprotein; Propolis, effect on apoptosis